DEVELOPMENT OF INTERACTIVE MULTIMEDIA ON THE PROCESS OF HINDU-BUDDHIST RELIGION AND CULTURE IN INDONESIA AT SMA NEGERI 1 LUBUK KELIAT - Deni (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2025)
This research aims to develop Interactive Multimedia on the Basic Competencies of the Theory of the Process of Development of Hindu-Buddhist Religion and Culture in Indonesia for grade X students at SMA Negeri 1 Lubuk Keliat. The results of the study show that the interactive multimedia products developed have good validity, practicality, and effectiveness. The results of expert validation (alpha test) showed an average assessment of 3.68, which is included in the valid category. The practicality test (beta test) resulted in an average assessment of 4.29, which is included in the very practical category. From the effectiveness test, the N-gain score of 0.64 shows effectiveness in the medium category, with an increase in student learning outcomes. With these results, this interactive multimedia is declared suitable for use as a learning medium in history subjects. It is recommended to integrate this multimedia into learning to increase students' motivation and understanding of the material.